Novel Homozygous Mutation of the Internal Translation Initiation Start Site of VHL is Exclusively Associated with Erythrocytosis: Indications for Distinct Functional Roles of von Hippel‐Lindau Tumor Suppressor Isoforms. Issue 11 (17th August 2015) - Bartels, Marije; van der Zalm, Marieke M.; van Oirschot, Brigitte A.; Lee, Frank S.; Giles, Rachel H.; Kruip, Marieke J.H.A.; Gitz‐Francois, Jerney J.J.M.; Van Solinge, Wouter W.; Bierings, Marc; van Wijk, Richard
<x xml:space="preserve">Abstract</x> Mutations in VHL are either associated with the von Hippel Lindau tumor predisposition syndrome or congenital secondary erythrocytosis. In this report we describe three patients with erythrocytosis in whom we identified a unique mutation that completely abolishes production of one of the two VHL isoforms. Our findings in these patients point to differences in the functional roles of the two VHL isoforms. that is likely to have important implications for the fields of both erythropoiesis and tumorigenesis.